The Relationship Between Young Women's Knowledge About Breast Cancer and Self-Breast Examination (Sadari) at SMA Negeri 1 Panyabungan Selatan Class - Nuraini, Elok; Hasida, May (Benih : Journal of Midwifery, 2023)
The objective of this study is to explore the association between young women's knowledge of breast cancer and their engagement in breast self-examination (BSE) practices at SMA Negeri 1 Panyabungan Selatan, located in the Panyabungan Selatan District of Mandailing Natal Regency in 2022. Employing a cross-sectional design, the research involved 150 female students from class X. Data collection utilized a questionnaire covering topics related to breast cancer awareness and BSE habits. The findings indicated a significant positive correlation (p < 0.05) between the knowledge level of adolescent girls regarding breast cancer and their regular practice of BSE. It was observed that those with a better understanding of breast cancer tended to perform BSE more frequently. These results underscore the pivotal role of health education in enhancing breast cancer awareness among adolescent girls and promoting the importance of regular BSE as a preventive measure. The implications of this study can inform the development of targeted intervention programs aimed at enhancing breast cancer awareness and health behaviors among adolescent girls in educational institutions and local communities.